School Heads’ Instructional Leadership and Emotional Competencies, and Teachers’ Work Performance in Selected Public Junior High Schools - Jimenez, Rica Grace; Galicia, Leomar S (Technium Education and Humanities, 2023)
The study aimed to determine the instructional leadership skills, emotional competencis, and teachers’ work performance in selected public junior high schools in the City Schools Division of Biñan City for the School Year 2021-2022. The researcher utilized the descriptive correlation approach and the study sample consisted of (256) teachers. The results of the study were based on the researcher-made questionnaire. The findings indicated that the school heads’ level of instructional leadership skills was interpreted as very high with a weighted mean of 3.61 while their level of emotional competencies was considered very high with an overall weighted mean of 3.41. In terms of teachers’ work performance, 206 of the respondents received a 4.500 to 5.00 range of scores in their IPCRF and were classified as Outstanding in level of work performance with an equivalent percentage of 80.47. Then 50 of the respondents received a 3.500 to 4.499 range of scores in their IPCRF and were classified as Very Satisfactory level of work performance with an equivalent percentage of 19.53. The findings revealed that a p-value of 0.000 was lower than 0.01 level of significance; therefore, there was a significant relationship between the school head’s level of instructional leadership skills and their level of emotional competencies. The findings revealed that a p-value of 0.050 was equal to the 0.05 level of significance; therefore, there is a significant relationship between the school head’s level of instructional leadership skills and teachers’ work performance. The results revealed a negligible relationship between teachers’ job performance and school leaders’ emotional abilities, with a Pearson r value of 0.093 and a p-value of 0.139 which is higher than 0.05 level of significance indicating no significant correlation between the teachers’ work performance and the level of emotional competencies of school heads. An action plan was proposed to strengthen the school heads’ instructional leadership skills and emotional competencies and to build more rapport with the teachers.